Features of nonlocal chiral quark models - Gómez Dumm, Daniel Alberto (2008)
Main features of nonlocal chiral quark models are discussed, focusing on the description of low energy phenomenology and the analysis of phase transitions at finite temperature and/or chemical potential. Applications to compact stars are commented.